La source - Minkus, L. 1826-1917 ([publisher not identified], 2011)
In Jean-Guillaume Bart's new choreography of La Source, a fantastical Persia becomes the backdrop for the tempestuous love affair between the hunter Djemil, the beautiful Nouredda, and the sprite Naïla. In his first creation for the Ballet of the Opéra national de Paris, principal dancer Jean-Guillaume Bart seized on a forgotten work originally premiered at the Opéra de Paris in 1866. Léo Delibes wrote a light and colorful score for his first ballet, a collaboration with Ludwig Minkus. The libretto by Arthur Saint-Léon and Charles Nuitter--who later wrote Coppélia--is steeped in Wagnerian Romanticism, Orientalism, and Shakespearean influences, and weaves together the real world with the world of elves, nymphs, and fantastical beings. In close collaboration with the playwright Clément Hervieu-Léger, Jean-Guillaume Bart returns La Source to its original freshness. The grand danced tale, poetic and virtuosic, is enhanced by Christian Lacroix's flamboyant costumes and Eric Ruf's evocative and moving staging
Keywords: Ballets; Webcast; Internet videos; Filmed ballets; Vidéos sur Internet; Ballets filmés